Production of fumaric acid from oil palm empty fruit bunch - U-thai, Panida; Vaithanomsat, Pilanee; Boondaeng, Antika; Talek, Anfal; Chuntranuluck, Sawitri (Asia-Pacific Journal of Science and Technology, 2016)
Oil palm empty fruit bunch (EFB), one of the most abundant agricultural residues in Thailand, is an attractive lignocellulosic material for value added agricultural products. They could be used as a raw material for cheap renewable feedstock to produce acids and many other value-added products. This research is to investigate the potential of EFB as a raw material for fumaric acid production through separate hydrolysis and fermentation (SHF) by the selected fungal isolate K20. Steam explosion was used in this study to pretreat the lignocellulosic material. A Cellic CTec2 enzyme (25 FPU/ml) was used to hydrolyze the pretreated material into glucose. Response surface methodology (RSM) based on central composite design (CCD) was applied to optimize the effect of the medium composition including solid loading, (NH4)2SO4 and Na2CO3 on fumaric acid concentration. The optimized medium consisted of (g/L): solid loading 166.70, (NH4)2SO4 0.29 and Na 2CO3 3.07. The maximum predicted value of fumaric acid concentration of 5.18 g/L was obtained, which corresponded with the observed values of 5.30 g/L<br style="font-style: normal; font-variant: normal; font-weight: normal; letter-spacing: normal; line-height: normal; orphans: 2; text-align: -webkit-auto; text-indent: 0px; text-transform: none; white-space: normal; widows: 2; word-spacing: 0px; -webkit-text-size-adjust: auto; -webkit-text-stroke-width: 0px;">